Gender and trade in Africa: Case study of Niger - Fofana, Ismaël; Odjo, Sunday P.; Traoré, Fousseini (International Food Policy Research Institute, 2019)
The evidence on the impact of trade liberalization on gender inequalities is not fully established yet, nor is the impact of gender inequalities on trade policy outcomes. Sociocultural norms, legal barriers, and socioeconomic disadvantages are the main gender-based discrimination that affect the distribution of trade benefits between men and women. This study applied to Niger assesses the distributional effects of trade reforms between men and women and sheds light on the impact of gender-based barriers on the outcome of trade reforms. The Common External Tariff (CET) of the Economic Community of West African States has guided Niger’s trade policy since its implementation in 2015. Thus, the study essentially assesses the impact of the CET reform on gender inequalities in Niger. Focusing on employment levels and earnings, the study finds an increased gender gap under the CET implementation, although the custom union reform leads to positive outcomes for both men and women compared to the baseline. Moreover, gender inequalities result in misallocation of resources in the economy and lead to a loss in economic opportunity for Niger. Thus, closing the gender gap in access to productive resources is likely to generate positive outcomes for Niger.